Cartilage Status in Relation to Return to Sports After Anterior Cruciate Ligament Reconstruction. (March 2013) - Van Ginckel, Ans; Verdonk, Peter; Victor, Jan; Witvrouw, Erik
Background: Osteoarthritis after anterior cruciate ligament (ACL) reconstruction receives much attention in orthopaedic science. Anterior cruciate ligament reconstruction is related to increased joint fluid volumes, bone marrow edema, and cartilage biochemical and morphological changes believed to cause fragile joint conditions. These joint conditions may not be able to adequately counter the imposed loads during sports. Hypothesis: At 6 months after surgery, knee cartilage displays inferior quality in ACL-reconstructed knees when compared with controls. This inferior quality is influenced by the time to return to sports and/or by the time to surgery. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Fifteen patients treated with isolated ACL reconstruction were compared with 15 matched controls. In all participants, a 3-T magnetic resonance imaging cartilage evaluation was performed entailing quantitative morphological characteristics (3-dimensional volume/thickness), biochemical composition (T2/T2* mapping), and function (after a 30-minute run: in vivo deformation including recovery). Nonparametric statistics were executed reporting median (95% CI). Results: No volume and thickness between-group differences existed. In patients, medial femur (FM) T2 was higher (45.44 ms [95% CI, 40.64-51.49] vs 37.19 ms [95% CI, 34.67-40.39]; P = .028), whereas T2* was lower in the FM (21.81 ms [95% CI, 19.89-22.74] vs 24.29 ms [95% CI, 22.70-26.26]; P = .004), medial tibia (TM) (13.81 ms [95% CI, 10.26-16.78] vs 17.98 ms [95% CI, 15.95-18.90]; P = .016), and lateral tibia (TL) (14.69 ms [95% CI, 11.71-16.72] vs 18.62 ms [95% CI, 17.85-22.04]; P < .001). Patients showed diminished recovery at 30 minutes after a 30-minute run in the FM (−1.60% [95% CI, −4.82 to −0.13] vs 0.01% [95% CI, −0.34 to 1.23]; P = .040) and at 30 (−3.76% [95% CI, −9.29 to −1.78] vs 0.04% [95% CI, −1.52 to −0.72]; P = .004) and 45 minutes after exercise (−1.86% [95% CI, −4.66 to −0.40] vs 0.43% [95% CI, −0.91 to 0.77]; P = .024) in the TL. Eight patients returned to sports at 6 months or earlier. Return before 5 months (3/8 patients) was associated with increased cartilage thickness (in TM, TL, and lateral femur [FL]), deformation (in FL), and delayed recovery after running (in FL and FM). Median surgical delay was 10 weeks (range, 5-17 weeks). Surgery within 10 weeks (9/15 patients) was also associated with delayed cartilage recovery (in FL and FM). For the other parameters, no significant relationships could be established for either return to sports or surgical delay. Conclusion: At 6 months after surgery, cartilage in patients with ACL reconstruction shows diminished quality and in vivo resiliency compared with controls. Caution is advised in an early return to sports especially when dealing with patients who received prompt surgery. Possibly, high impacts on this qualitatively diminished cartilage might play a role in the development of osteoarthritis in ACL reconstruction. Replication in larger samples and follow-up are warranted.